Penentuan Kadar Garam Kultur Hara untuk Seleksi Toleransi Salinitas pada Padi Lokal Bengkulu - Rustikawati, Rustikawati; Simarmata, Marulak; Turmudi, Edhi; Herison, Catur (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2014)
Bengkulu province area elevating from 0 m to over 1000 m above sea level possesses high rice germplasm diversity. To obtain salinity controlling gene(s) from those germplasm, it is required to determine a suitableprotocol. This research was objected to determine NaCl concentration to select Bengkulu rice landraces. The standard most salinity tolerant genotype used in this research was ’Kuning’, a local variety usually grown on tidal area of Seluma Regency for generations. The growing media was Yoshida nutrient culture supplemented with a series of NaCl concentration of 0, 2000, 4000, 6000, 8000 or 10000 ppm. Observation was done every 2 days to find out the response pattern of rice seedling growth on different NaCl concentration. NaCl stress level was determined at 90% seedling dead (LC90) at the eighth day. The results showed that the increase of plantheight was deceased at concentration of 6000 ppm. Based on the mathematical equation generated from the percent mortality data distribution, the LC90 was at 3910 ppm NaCl concentration.